Estimulantes radiculares: efectos en la producción del cultivo de banano (musa x paradisiaca) - Siguencia Medina, Marcos Vinicio (Machala : Universidad Técnica de Machala, 2022)
In Ecuador, one of the main axes that the country has for economic development is the banana sector, generating sources of work, mainly for families located on the Ecuadorian coast, in the external market this item is one of the main export products with premium quality when the conditions of the crop and its agricultural practices are properly managed. Nutrition is essential for the correct development of bananas, their main pathways for nutrient absorption are the roots, their care and the optimal applications of agrochemicals guarantee more profitable harvests in less time. The root stimulants applied in the plantation are characterized by the activation of the root mass, generating healthy and functional roots during the development of the crop to obtain greater productivity. The main objective of this study was to evaluate the effects of root stimulants on banana production. The variables were: (AHJ) height of the son, (AHJ) stem of the son, (PRS) percentage of healthy roots, (PRD) percentage of damaged roots, (PRC) percentage of dry roots, (PTR) total weight of roots, (PRAC) total weight of the bunch, (PTM) total weight of hands, (PRQR) weight of the bunch rachis, (NMR) number of hands per bunch, (NDMS) number of fingers second sun hand. The present study was carried out on the María Paola farm, whose plantation corresponds to the Cavendish variety already established in an area of 7 ha, located in the "Iberia" parish belonging to the El Guabo canton, El Oro province. The experimental design that was used was a Randomized Complete Block Design, where 14 treatments described below were applied: T1 (Terrasor-Foliar, Aminoquelant-Ca, Biochar); T2 (Terrasor-Foliar, Aminoquelant-Ca, Pow Humus); T3 (Terrasor-Foliar, Aminoquelant-Ca, Active 80 Ds); T4 (Inicium, Aminoquelant-Ca); T5 (Inicium, Aminoquelant-Ca, Biochar); T6 (Inicium, Terrasor-Foliar); T7 (Equilibrium); T8 (Equilibrium, Biochar); T9 (Equilibrium, Pow Humus); T10 (Equilibrium, Active 80 Ds); T11 (Raizal, Biozyme-Tf, Carbox); T12 (Root-Most, Active 80 Ds); T13 (Equilibrium, Aminoquelant-Ca, Aminoquelan-Zn); and T14 (Equilibrium, Aminoquelant-Ca, Aminoquelan-Zn, Biochar). The rooting products were applied with manual pumps to recently born plants, managing a dosage of 5 passes in front of the crescent-shaped son. The root samples were obtained from the mother-child front at a distance of 40 cm, a hole of 20x20 cm in length with a depth of 30 cm was made. All the data was analyzed in the SPSS Statistics 22 software, through a one-factor ANOVA and the Tukey test, managing a significance of (0.05). The best treatment regarding the height of the child (AHJ) was T14 where it was applied (Equilibrium, Aminoquelant-Ca, Aminoquelan-Zn, Biochar ), obtaining an average of 5.06 meters in height, for the stem variable (FHJ) also T14 presented good results with a value of 120.22 cm of stem, in the statistical analysis of the roots the treatments that presented the best results in the PRS and PTR variable, was T13 (Equilibrium, Aminoquelant-Ca, Aminoquelan-Zn) and T14 (Terrasor-Foliar, Aminoquelant-Ca, Biochar), it was also identified that treatment T3 and T4 showed a lower percentage of damaged roots, and T1 together with T2 obtained a lower percentage of dry roots, at harvest the variable PRAC the T13 treatment where it was applied (Equilibrium, Aminoquelant-Ca, Aminoquelan-Zn), better results were obtained with an average of 82.19 lb, for the PRQR variable the same treatment obtained 9.2 lb, likewise for the PTM variable that I get to mark 72.99 lb, in the NMR variable the T1 3 and T3 reflected the same average of 8 hands per cluster, surpassing the rest of the treatments. In the NDMS variable, the one that presented the best results was treatment T3 where it was applied (Terrasor-Foliar, Aminoquelant-Ca, Active 80 Ds) reaching a value of 26.2 fingers, followed by T8 (Equilibrium, Biochar) and T5 (Inicium, Aminoquelant-Ca, Biochar) showed positive results, obtaining an average of 23.8 and 23.6 fingers.
En Ecuador, uno de los principales ejes que tiene el país para el desarrollo económico es el sector bananero, generando fuentes de trabajado, principalmente para las familias ubicadas en la costa ecuatoriana, en el mercado externo este rubro es uno de los principales productos de exportación con calidad premium cuando se maneja de forma adecuada las condiciones del cultivo y sus prácticas agrícolas. La nutrición es fundamental para el correcto desarrollo del banano, sus vías principales de absorción de nutrientes son las raíces, su cuidado y las óptimas aplicaciones de agroquímicos garantizan cosechas más rentables en menor tiempo. Los estimulantes radiculares aplicados en la plantación se caracterizan por la activación de la masa radicular, generando raíces sanas y funcionales durante el desarrollo del cultivo para obtener mayor productividad. El objetivo principal de este estudio fue evaluar los efectos de los estimulantes radiculares en la producción de banano. Las variables fueron: (AHJ) altura del hijo, (AHJ) fuste del hijo, (PRS) porcentaje de raíces sanas, (PRD) porcentaje de raíces dañadas, (PRC) porcentaje de raíces secas, (PTR) peso total de raíces, (PRAC) peso total del racimo, (PTM) peso total de manos, (PRQR) peso del raquis del racimo, (NMR) número de manos por racimo, (NDMS) número de dedos segunda mano de sol. El presente estudio se realizó en la finca María Paola, cuya plantación corresponde a la variedad Cavendish ya establecida en un área de 7 ha, ubicada en la parroquia la “Iberia” perteneciente al cantón El Guabo, provincia El Oro. El diseño experimental que se empleó fue Diseño de bloques Completo al Azar, donde se aplicaron 14 tratamientos descritos a continuación: T1 (Terrasor-Foliar, Aminoquelant-Ca, Biochar); T2 (Terrasor-Foliar, Aminoquelant-Ca, Pow Humus); T3 (Terrasor-Foliar, Aminoquelant-Ca, Activo 80 Ds); T4 (Inicium, Aminoquelant-Ca); T5 (Inicium, Aminoquelant-Ca, Biochar); T6 (Inicium, Terrasor-Foliar); T7 (Equilibrium); T8 (Equilibrium, Biochar); T9 (Equilibrium, Pow Humus); T10 (Equilibrium, Activo 80 Ds); T11 (Raizal, Biozyme-Tf, Carbox); T12 (Root-Most, Activo 80 Ds); T13 (Equilibrium, Aminoquelant-Ca, Aminoquelan-Zn); y T14 (Equilibrium, Aminoquelant-Ca, Aminoquelan-Zn, Biochar). Los productos enraizantes fueron aplicados con bombas manuales a plantas recién paridas, manejando una dosificación de 5 pasadas frente al hijo en forma de medialuna. Las muestras de raíces se la obtuvo frente madre-hijo a una distancia de 40 cm, se hizo un boquete de 20x20 cm de longitud con una profundidad de 30 cm. Todos los datos se analizaron en el software SPSS Statistics 22, mediante un ANOVA de un factor y la prueba Tukey manejando una significancia del (0,05). El mejor tratamiento respecto a la altura del hijo (AHJ) fue el T14 donde se aplicó (Equilibrium, Aminoquelant-Ca, Aminoquelan-Zn, Biochar ), obteniendo una media de 5,06 metros de altura, para la variable fuste (FHJ) también T14 presento buenos resultados con un valor de 120,22 cm de fuste, en el análisis estadístico de las raíces los tratamientos que mayores resultados presentaron en la variable PRS y PTR, fue el T13 (Equilibrium, Aminoquelant-Ca, Aminoquelan-Zn) y T14 (Terrasor-Foliar, Aminoquelant-Ca, Biochar), también se identificó que el tratamiento T3 y T4 mostraron un menor porcentaje de raíces dañadas, y el T1 junto con T2 obtuvieron menos porcentaje de raíces secas, en la cosecha la variable PRAC el tratamiento T13 donde se aplicó (Equilibrium, Aminoquelant-Ca, Aminoquelan-Zn), se obtuvo mejores resultados con una media de 82,19 lb, para la variable PRQR el mismo tratamiento obtuvo 9,2 lb, así mismo para la variable PTM que llego a marcar 72,99 lb, en la variable NMR el T13 y T3 reflejaron la misma media de 8 manos por racimo superando al resto de tratamientos, en la variable NDMS el que mejor presento resultados fue el tratamiento T3 donde se aplicó (Terrasor-Foliar, Aminoquelant-Ca, Activo 80 Ds) llegando a un valor de 26,2 dedos, siguiéndole el T8 (Equilibrium, Biochar) y T5 (Inicium, Aminoquelant-Ca, Biochar) evidenciaron resultados positivos obteniendo una media de 23,8 y 23,6 dedos.
Keywords: BIOCHAR; PRÁCTICAS AGRÍCOLAS; MASA RADICULAR; ESTIMULACIÓN; VARIEDAD; PRODUCTIVIDAD; NUTRICIÓN